Análise de escore de cálcio e angiotomografia coronariana e suas correlações com doença arterial coronariana - Andrade, Augusto Cesar Monte (2018)
Introduction: The evaluation of coronary atherosclerotic anatomy and charge, previously only possible through invasive examinations, now we can be obtained noninvasively through coronary angiotomography (CTA). Coronary calcium score, in recent studies, added a prognostic capacity to traditional risk factors. However, divergent literature data demonstrate that the calcium score (CS) did not add incremental prognostic information to CTA. Objectives: Analyze calcium score, anatomical patterns and physiological characteristics in adult patients with coronary disease through CTA. Methods: This is a descriptive, longitudinal and retrospective study, based on the analysis of reports of CTA from a secondary database, the sample was composed of individuals of both genders over 18 years of age. Results: The sample consisted of 45 men (49.45%) and 46 women (50.55%), with a middle age of 57.80 ± 13.02 years. Analyzes of 49.45% resulted in a positive CS, and 24% were superior to 400. 36 (39.5%) of the 91 studies analyzed presented some degree of coronary obstruction. 06 patients had lesions in only 01 vessels, 18 in two vessels, 9 in 3 vessels and 03 multiarterial. Of the 36 patients, 15 (41.6%) had at least 01 vessels with occlusion greater than 50%. It was observed that 03 (3.29%) patients presented zero CS and arteriosclerotic lesion. Being 01 with occlusion inferior to 50% and 02 with occlusion greater or equal to 50%. Conclusions: The prevalence of atherosclerotic lesions was high in the study population. The CS was not able to add incremental prognostic information to CTA.